Gender perspective in psoriasis: a scoping review and proposal of strategies for improved clinical practice by European dermatologists - Alvaro Gonzalez-Cantero, MD, PhD; María Magdalena Constantin, MD; Annunziata Dattola, MD; Tom Hillary, MD; Elise Kleyn, MD, PhD; Nina Magnolo, MD (Wolters Kluwer, 2023)
Background:. The prevalence of psoriasis is similar between men and women; however, evidence exists of sex- and gender-related differences in disease expression, impact, coping, and needs of patients with psoriasis. These differences are essential and should be considered in clinical practice and research. Objective:. To compile available evidence on sex- and gender-related differences in psoriasis, identify the most critical gaps in clinical practice and research, and use it to propose strategies for improved clinical practice. Methods:. Six European dermatologists selected the topics to consider according to their relevance in the dermatology setting with the support of methodologists. Evidence on sex- and gender-related differences was obtained by a scoping review based on search strategies in Medline and Cochrane Library from inception to October 2021 using the following terms: arthritis, psoriatic, psoriasis, gender, and sex. The panel discussed the results and proposed strategies by consensus. Results:. The scoping review identified broad themes: (1) clinical expression, (2) severity and patient-reported outcomes, (3) psychosocial impact, (4) access to treatments and propensity to treat, (5) comorbidities, and (6) treatment effect. The strategies are based on these broad themes. Limitations:. No risk of bias assessment was done due to the scoping nature of the review. Conclusion:. This review offers insights into gender differences in psoriasis, providing a foundation for improving clinical practice and patient outcomes.